The psychology of balancing gains and losses for self and the environment: Evidence from a carbon emission versus travel time tradeoff task. (April 2021) - Bökman, Fredrik; Andersson, Hanna; Sörqvist, Patrik; Ahonen-Jonnarth, Ulla
Abstract: If human behavior is to become more sustainable, people will have to be willing to sacrifice personal gains and benefits for the sake of sustainability. Decisions will have to involve making tradeoffs between what is good for the self and what is good for sustainability. In the present paper, we studied the psychology of such tradeoffs in the context of a carbon dioxide (CO2 ) emission versus travel time tradeoff task. The experiment investigated how intrinsic motivational factors (environmental concern), extrinsic motivational information (a normative message) and extrinsic motivation-neutral information (anchors) influence these tradeoffs. The results revealed that extrinsic factors interact in their effects on tradeoffs such that participants were willing to travel for a longer time for the benefit of less CO2 emissions when they were externally motivated by a normative message, but only when this motivational emphasis was combined with a high anchor. Furthermore, this interaction was particularly strong in participants with high environmental concern. We conclude that extrinsic and intrinsic motivational factors interact in their effect on making people willing to accept personal losses in exchange for sustainability gains and that these motivational factors may have to be combined with further extrinsic information to influence decisions. Highlights: Experiment with tradeoffs between reduced CO2 emissions and increased travel times. Explicit tradeoffs between a pro-self and a pro-environment attribute. A high anchor and a normative message results in longer travel times. Stronger interaction between anchor and message with higher environmental concern.